Evidence-based orthopedics - Bhandari, Mohit; Adili, Anthony (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
Surgical orthopedic procedures such as hip replacements, arthroscopy or knee replacements are surrounded by pre- and post-operative complications, and there are varying different methods for the procedures themselves. This book, for the first time, brings together the best evidence for treatments as well as any complications. Not only does it cover the evidence base for orthopedic surgery, but also orthopedic conditions requiring medical treatment, and pediatric orthopedics. Using the approved EBM methodology, and edited by teachers of evidence-based medicine, this is a genuine EBM textbook for all orthopedic specialists and trainees.
Evidence-Based Orthopedics; Contents; Contributors; Foreword; Preface; Abbreviations; Section I: Methodology of Evidence-Based Orthopedics; 1: Principles of Evidence-Based Orthopedics; 2: Understanding Hierarchies of Evidence and Grades of Recommendation; 3: Critical Appraisal Tools for Surgeons; 4: Understanding Diagnosis, Therapy, and Prognosis; 5: Systematic Reviews and Meta-Analysis; 6: Economic Analysis; Section II: Orthopedic Medicine; 7: Osteoporosis and Metabolic Disorders; 8: Thromboprophylaxis in Orthopedic Practice; 9: Blood Transfusion; 10: Wound Infections; 11: Gouty Arthritis.
Includes bibliographical references and index.
Print version record.
Keywords: Orthopedic surgery; Musculoskeletal system -- Wounds and injuries; Evidence-based medicine; MEDICAL -- Surgery -- General; Evidence-based medicine; Musculoskeletal system -- Wounds and injuries; Orthopedic surgery; Bone and Bones -- surgery; Evidence-Based Medicine; Fractures, Bone -- surgery; Joints -- surgery; Orthopedic Procedures; Electronic books; Electronic books